CISD2 Promotes Resistance to Sorafenib-Induced Ferroptosis by Regulating Autophagy in Hepatocellular Carcinoma - Li, Bowen; Wei, Shibo; Yang, Liang; Peng, Xueqiang; Ma, Yingbo; Wu, Bo; Fan, Qing; Yang, Shuo; Li, Xinyu; Jin, Hongyuan; Tang, Shilei; Huang, Mingyao; et al. (Frontiers in Oncology, 2021)
Purpose: Sorafenib is a multi-kinase inhibitor that is used as a standard treatment for advanced hepatocellular carcinoma (HCC). However, the mechanism of sorafenib resistance in HCC is still unclear. It has been shown that CISD2 expression is related to the progression and poor prognosis of HCC. Here, we show a new role for CISD2 in sorafenib resistance in HCC. Methods: Bioinformatic analysis was used to detect the expression of negative regulatory genes of ferroptosis in sorafenib-resistant samples. The concentration gradient method was used to establish sorafenib-resistant HCC cells.¬¬ Western blot was used to detect the protein expression of CISD2, LC3, ERK, PI3K, AKT, mTOR, and Beclin1 in HCC samples. Quantitative real-time PCR (qPCR) was used to detect gene expression. CISD2 shRNA and Beclin1 shRNA were transfected to knock down the expression of the corresponding genes. Cell viability was detected by a CCK-8 assay. ROS were detected by DCFH-DA staining, and MDA, GSH were detected with a Lipid Peroxidation MDA Assay Kit and Micro Reduced Glutathione (GSH) Assay Kit, respectively. Flow cytometry was used to detect apoptosis and the levels of ROS and iron ions. Results: CISD2 was highly expressed in HCC cells compared with normal cells and was associated with poor prognosis in patients. Knockdown of CISD2 promoted a decrease in the viability of drug-resistant HCC cells. CISD2 knockdown promoted sorafenib-induced ferroptosis in resistant HCC cells. The levels of ROS, MDA and iron ions increased, but the change in GSH was not obvious. Knockdown of CISD2 promoted uncontrolled autophagy in resistant HCC cells. Inhibition of autophagy attenuated CISD2 knockdown-induced ferroptosis. The autophagy promoted by CISD2 knockdown was related to Beclin1. When CISD2 and Beclin1 were inhibited, the effect on ferroptosis was correspondingly weakened. Conclusion: Inhibition of CISD2 promoted sorafenib-induced ferroptosis in resistant cells, and this process promoted excessive iron ion accumulation through autophagy, leading to ferroptosis. The combination of CISD2 inhibition and sorafenib treatment is an effective therapeutic strategy for resistant HCC.